2019
DOI: 10.1186/s12978-019-0820-8
|View full text |Cite
|
Sign up to set email alerts
|

The power of peers: an effectiveness evaluation of a cluster-controlled trial of group antenatal care in rural Nepal

Abstract: BackgroundReducing the maternal mortality ratio to less than 70 per 100,000 live births globally is one of the Sustainable Development Goals. Approximately 830 women die from pregnancy- or childbirth-related complications every day. Almost 99% of these deaths occur in developing countries. Increasing antenatal care quality and completion, and institutional delivery are key strategies to reduce maternal mortality, however there are many implementation challenges in rural and resource-limited settings. In Nepal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 15 publications
2
55
1
Order By: Relevance
“…We hypothesize that non-use of family planning in our sample may be due to a low perceived risk of pregnancy before a return of menses, as a systematic review found [38]. Like the study in Nepal [31], we found no quantitative data showing an increase in facility delivery; the use of facilities for delivery at baseline was high (89%), making changes harder to see. In contrast, through our qualitative data, health providers, CHVs, and county staff reported that GANC led to a perceived increase in rates of facility delivery at project sites.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…We hypothesize that non-use of family planning in our sample may be due to a low perceived risk of pregnancy before a return of menses, as a systematic review found [38]. Like the study in Nepal [31], we found no quantitative data showing an increase in facility delivery; the use of facilities for delivery at baseline was high (89%), making changes harder to see. In contrast, through our qualitative data, health providers, CHVs, and county staff reported that GANC led to a perceived increase in rates of facility delivery at project sites.…”
Section: Discussioncontrasting
confidence: 54%
“…This contradicts what is generally found in the literature [17,23,34,35], which has reported improvements in all aspects of knowledge. A recent study in Nepal [31] also found that knowledge of danger signs signi cantly improved, but knowledge of birth preparation decreased, from baseline to endline. Our qualitative data revealed that participating women identi ed learning as the aspect they most valued in GANC; they appreciated the tips and information and an understanding of the "why" in addition to the "what."…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations